Changes in the house sparrow population in Britain - Summers-Smith, Denis J. (Zielona Góra: University of Zielona Góra, Institute of Biotechnology & Environmental)
The number of House Sparrows has declined markedly in mid-latitude western Europe in the last 25-30 years. This was first noticed in Britain in farmland about 1979, though after a fall of about 60% the population appears to have stabilised at this lower level. It is now generally accepted that this decline was a consequence of reduction in the availability of food resulting from intensification of agricultural practices.
Keywords: wróblowe; ornitologia; Wielka Brytania